Intervention and Sampling Trends in Literacy Research for Young Augmentative and Alternative Communication Users: A Scoping Review. - Benson-Goldberg, Sofia; Erickson, Karen (Journal of Speech, Language & Hearing Research, 2025)
Purpose: This scoping review aims to characterize the body of literature addressing literacy interventions involving young children (ages 2–8 years) who use or would benefit from aided augmentative and alternative communication (AAC). Method: A systematic search was conducted in six databases. The search yielded 33 intervention studies. Participant characteristics (i.e., age, gender, communication profile) were charted along with intervention characteristics (i.e., focus, outcome variables, settings, interventionists, aided AAC materials). Results: Findings provide insight into intervention and sampling trends. Specifically, studies predominantly investigated shared reading interventions to support expressive communication with children who were already symbolic communicators. There was a noticeable lack of studies involving children with multiple disabilities including intellectual disabilities. Conclusions: The review highlights the necessity for more inclusive research that represents the diverse communication and disability profiles of young children who use or would benefit from aided AAC. Future studies should aim to include participants with varying abilities and access methods. Additionally, the emphasis on emergent literacy, particularly shared reading, should be expanded to include comprehensive emergent literacy skills such as generative writing, phonological awareness, and language comprehension. This broader focus will better support the literacy development of young children who use or would benefit from aided AAC.